2004
DOI: 10.1023/b:fopl.0000019652.32607.08
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Anomalous Brillet and Hall Experimental Result

Abstract: The persistent, second order, anomalous signal found in the Brillet and Hall experiment is derived by applying 4D differential geometry in the rotating earth frame. By incorporating the off diagonal time-space components of the rotating frame metric directly into the analysis, rather than arbitrarily transforming them away, one finds a signal dependence on the surface speed of the earth due to rotation about its axis. This leads to a Brillet-Hall signal prediction in remarkably close agreement with experiment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Thus, the round trip speed of light in any direction orthogonal to the rotating frame local velocity is c. (A more sophisticated analysis leading to this result can be found in Ref. [40], p. 130.)…”
Section: Analyzing Sagnac Time Differencementioning
confidence: 87%
See 2 more Smart Citations
“…Thus, the round trip speed of light in any direction orthogonal to the rotating frame local velocity is c. (A more sophisticated analysis leading to this result can be found in Ref. [40], p. 130.)…”
Section: Analyzing Sagnac Time Differencementioning
confidence: 87%
“…11 for an explanation of how this earth frame signal effectively averaged out to zero for the cosmic light speed isotropy result.) Most subsequent researchers have considered this signal to be anomalous, though others [39] , [16] , [40] have suggested that something significant may be behind it, i.e., true light speed anisotropy due to idiosyncrasies of rotating frames.…”
Section: Brillet and Hallmentioning
confidence: 99%
See 1 more Smart Citation
“…where, e 1 and e 2 here do not, in general, have to be orthogonal, e i andê i point in the same direction for each index i, and carets over component indices indicate physical components. Substituting (25) into (27), one readily…”
Section: Appendix C Physical Vs Coordinate Componentsmentioning
confidence: 99%
“…When this is done, not only can the Sagnac effect be derived (as shown below), but all other observed rotating frame effects can be, as well. (See Klauber [15] , [16] , [20] , [21] , [22] , [23] , [24] , [25].) Further, the geometric foundation of relativity theory remains intact.…”
Section: Introductionmentioning
confidence: 99%